Speech-language-hearing teletherapy for children with autism spectrum disorders during the covid-19 pandemic - Ariely Carla Felix da Silva Santos; Ivana Arrais de Lavor Navarro Xavier; Bianca Arruda Manchester de Queiroga; Angélica Galindo Carneiro Rosal; Rafaella Asfora Siqueira Campos Lima; Ana Cristina de Albuquerque Montenegro (Revista CEFAC, 2023)
ABSTRACT This paper aimed to investigate the contribution of speech-language-hearing teletherapy to the development of communication skills in children with autism spectrum disorders during the coronavirus-19 pandemic. This qualitative, interventive, longitudinal case series study analyzed data from the medical records of patients, based on instructions given to their families via speech-language-hearing teletherapy during social isolation. It was part of a public outreach program conducted in a speech-language-hearing teaching clinic, aiming to analyze results in the field of language. All children progressed in various aspects, such as the development of communication skills, expanded vocabulary, increased naming and asking, morphosyntactic development, and advancements in the use of augmentative and alternative communication. Also, shared attention and eye contact increased, the interaction with the family improved, and inadequate behaviors decreased; there was greater autonomy in daily routine and greater attention during activities; increased interest in toys during play and longer and more frequent playing, associated with decreased screen time. In conclusion, the results demonstrated progress in communication and social interaction after the speech-language-hearing teletherapy for children presented with autism spectrum disorders during the coronavirus-19 pandemic.